Answer:
log1/8
Step-by-step explanation:
2x-8(-7-x)=6
2x+56+8x=6
10x=-50
x=-5
y=-7-(-5)
y=-2
(-5,-2)
Answer:
13.3 ft
Step-by-step explanation:
24² - 20² = d²
d = √(576 - 400) = √176 = 13.26649... ≈ 13.3 ft.
Answer:
m = 2, n = - 3
Step-by-step explanation:
Given the 2 equations
2m + 3n = - 5 → (1)
5m + 3n = 1 → (2)
Subtract (2) from (1) term by term to eliminate n
2m - 5m = - 5 - 1
- 3m = - 6 ( divide both sides by - 3 )
m = 2
Substitute m = 2 into either of the 2 equations and solve for n
Substituting into (1)
2(2) + 3n = - 5
4 + 3n = - 5 ( subtract 4 from both sides )
3n = - 9 ( divide both sides by 3 )
n = - 3